Collaboration as a Key Feature of Equine Evidence-Based Research: A Laminitis Case Study - Wylie, Claire (Veterinary Evidence, 2017)
Abstract It is widely believed that laminitis poses a threat to the health and welfare of all Equidae; however, there is a paucity of evidence-based research on fundamental aspects of the disease, including how commonly it occurs, its clinical presentation and those animals at greatest risk. Following generous funding from World Horse Welfare, we have produced a programme of work over the last eight years to improve the evidence base regarding the epidemiology of laminitis. This began with systematic reviews regarding the frequency of [1], and risk factors for [2], naturally-occurring laminitis which informed the planning and conduct of prospective veterinary practice-level cohort and nested case-control studies of veterinary-diagnosed laminitis in British horses. Laminitis research tools, disease frequency estimates [3], potential novel modifiable risk factors [4] and guidelines for the differential diagnosis of laminitis [5] have all resulted from these now published, peer-reviewed studies. Ongoing work gathers further information on owner-reported laminitis cases by means of a prospective individual animal-level cohort study design, implemented through the use of web-based data collection (www.careaboutlaminitis.org.uk). Each step of the generation of this evidence-based data has demanded high levels of collaborative effort between charitable bodies, epidemiologists, information technology consultants, public relation officers, laminitis researchers, veterinary practitioners and horse owners. This talk will outline the methods we used to gather evidence-based data in the equine field, highlight the challenges and lessons we have learnt, and emphasise the crucial role the veterinary practitioner can play in both providing and using such evidence-based data.